Tinjauan Yuridis Terhadap Tindak Pidana Pengancaman dalam Undang-Undang Informasi dan Transaksi Elektronik: Studi Kasus Pengadilan Negeri Koto Baru - Sry Wahyuni; Elwidarifa Marwenny (UIR Law Review, 2020)
The subject matter of this research is the Juridical Review of the Crime of Threats in the Information and Electronic Transactions Law (Case Study of the Koto Baru District Court). This issue is divided into two sub-discussions, first, how is the application of material crimes against criminal acts of threats in the Law on Information and Electronic Transactions, second, how are judges' legal considerations in imposing crimes against threats of threats in the Law on Electronic Information and transactions. The method used in this research is to use a normative juridical problem approach. about the problem that is the object of the problem.The results showed that efforts to apply sanctions were made to overcome the perpetrators of extortion and threats, namely: firmly enforcing the existing positive laws. For subjective positive law enforcement, it may be necessary to have instruments or law enforcers who have the instinct of justice, namely "Judges" who decide all existing cases. The research implication is: it is hoped that the inculcation of social values ​​and norms in society in using social media and in UUITE is not trapped in behavior that plunges them into criminal acts / crimes, it is also hoped that the Panel of Judges in deciding cases must consider more The facts of the trial, the elements of the offense, and the consideration of the severity of the crime with reference to the defendant's situation and the victim's loss.